Evaluation of application potential of dye-decolorizing peroxidase from Bacillus amyloliquefaciens in bioremediation of paper and pulp mill effluent - Ren, Jing; Li, Xiaodan; Zhang, Weitao; Li, Zhuofan; Wang, Quan; Li, Shuna; Wang, Shuxiang; Li, Hongya (Frontiers in Microbiology, 2022)
Pulp and paper mill effluent is rich in recalcitrant and toxic pollutants compounds and causes pollution. To find an efficient biocatalyst for the treatment of effluent, a dye-decolorizing peroxidase from Bacillus amyloliqueficiens MN-13, which is capable of degrading lignin, was used for the bioremediation of paper and pulp mill effluent. The dye-decolorizing peroxidase from Bacillus amyloliqueficiens (BaDyP) exhibited high-redox potential to 2, 2’-azinobis (3-ethylbenzothiazoline-6-sulfonic acid ammonium salt (ABTS), veratryl alcohol, Mn2+, reactive blue 19, reactive black 5 and lignin dimer guaiacylglycerol-beta-guaiacyl ether (GGE). When GGE was used as substrate, BaDyP broke β-O-4 bond of GGE and then oxidize Cα to generate vanillin. The Km values for ABTS and veratryl alcohol were 2.19 mM and 0.07 mM, respectively. The Vmax for ABTS and veratryl alcohol were 1.8 mM/min and 14.12 mM/min, respectively. The BaDyP-mediated treatment of pulp and paper mill effluent led to significant reduction of chemical oxygen demand (COD) and color. When 5% (v/v) of effluent was treated with BaDyP for 12 h at 30 ℃ and pH 2, the removal of COD, color and lignin were achieved at 82.7%, 80.2% and 78.20%, respectively. In detoxification assay, the seeds of Vigna unguiculata grown in treated effluent showed a significant increase in germination rate from 66.7% (untreated effluent) to 90%, and in radicle length from 0.68 cm (untreated effluent) to 1.26 cm respectively. In the meanwhile, the inhibition of Escherichia coli and Bacillus subtilis by the treated effluent reduced significantly as compared to untreated effluent, indicating high detoxification performance of BaDyP for the treatment of pulp and paper mill effluent. The findings suggest that BaDyP is a potential catalyst for bioremediation of pulp and paper mill effluent, as it is effective in substantial lowering of pollutants load as well as reduces COD, color and toxicity of effluent.